2006
DOI: 10.1016/j.clinbiochem.2005.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Population distribution of high sensitivity C-reactive protein values in Aboriginal Australians: A comparison with other populations

Abstract: Objectives: To examine the distribution of C-reactive protein (CRP) values in Aboriginal Australians and its relation to age and gender. Methods: High sensitivity CRP levels were measured in 954 Aboriginal participants aged 5-74 years. Fractional polynomial regressions were used to explore the relationship between CRP and age. Results: CRP values changed with age and reached its lowest level around 10 years and then increased with age. Geometric means of CRP were 7.3 (95% confidence interval (CI): 6.6, 8.1) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 39 publications
2
18
0
3
Order By: Relevance
“…In addition, they also have higher CRP levels than other populations [13]. The strong and independent association between CRP and the risk of developing diabetes suggests that inflammation in may be partly responsible for the increased risk of diabetes in this population.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In addition, they also have higher CRP levels than other populations [13]. The strong and independent association between CRP and the risk of developing diabetes suggests that inflammation in may be partly responsible for the increased risk of diabetes in this population.…”
Section: Discussionmentioning
confidence: 86%
“…The distributions of CRP values vary significantly among race/ethnic groups [3] and [12]. The CRP level in Aboriginal population is much higher than that reported in other populations [13]. However, there is little information on inflammatory markers in high risk populations.…”
mentioning
confidence: 86%
“…Aboriginal people than populations in USA, Germany, Japan, Thailand and UK and that CRP changes with age [286]. Consistent with this study, Claes et al (2014) also found that median CRP levels were higher in Indigenous Australian CKD patients than non-Indigenous Australian CKD patients [287].…”
Section: Crp and Ckd In Indigenous Australianssupporting
confidence: 79%
“…This suggests the CRP and CKD association observed in our study is not exclusive to remote indigenous Australian communities. A study by Wang and Hoy in this same Indigenous community showed median CRP levels were higher than in several other international populations [286]. More recently Claes et al, in a sample of over 23,000…”
Section: Discussionmentioning
confidence: 97%
“…It is a marker for inflammation as it increases in the presence of inflammation in the body. A few studies have identified high-level CRP among Aboriginal people in Australia (195,196). These studies also reported that CRP levels were higher in females than males.…”
Section: High Waist Circumference: Older Agementioning
confidence: 89%